Polyphenol from foxtail millet bran alleviates experimental colitis in mice by remodulating intestinal fungal community - Shuiling He; Ruipeng Yang; Jiangying Shi; Ning An; Shuhua Shan; Zhuoyu Li; Xiushan Dong (Food Science and Human Wellness)
Inflammatory bowel disease (IBD) is a chronic relapsing-remitting systemic disease of the gastrointestinal tract, characterized by an inflammatory process. Gut mycobiota community dysbiosis has been reported that is closely related to the development of IBD. Our previous findings indicated that polyphenol of the inner shell (BPIS) from foxtail millet bran could restore the gut microbiome and inhibit the progress of colorectal cancer (CRC). In the present study, we studied the anti-inflammatory potential of BPIS in the dextran sodium sulfate (DSS)-induced mouse colitis model. Data suggested that BPIS alleviated experimental colitis by restoring body weight, colonic length and protecting the epithelial architecture from damage by DSS. Moreover, we found that BPIS strengthened the gut barrier function and inhibited the activation of Wnt1/β-catenin pathway. Gene sequence analysis indicated that BPIS remodeled the overall structure of the gut mycobiota from colitis mice toward that of the normal counterparts, including 1 phylum and 9 genera. Interestingly, BPIS significantly increased the abundance of Aspergillus ruber. It further verified that BPIS significantly promoted the growth of A. ruber in vitro. Collectively, BPIS has great potential to develop into an effective against IBD drug.